2020
DOI: 10.1016/j.omtn.2020.09.034
|View full text |Cite
|
Sign up to set email alerts
|

circ_2858 Helps Blood-Brain Barrier Disruption by Increasing VEGFA via Sponging miR-93-5p during Escherichia coli Meningitis

Abstract: Meningitic Escherichia coli invasion of the host brain can lead to increased blood-brain barrier (BBB) permeability. Circular RNAs (circRNAs) are non-coding RNAs, highly abundant in the brain, that are widely involved in the pathological processes of central nervous system (CNS) disorders; however, whether circRNAs participate in the regulation of BBB permeability during E. coli meningitis remains unknown. Here, we identified a novel circRNA, circ_2858, that was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Consistently, miR-17-5p was also decreased in hBMECs in response to meningitic E. coli infection, as observed in our previous work [46]. Here, we showed that miR-17-5p was one of the competitive-sponging targets of lncRSPH9-4 and miR-17-5p could bind to 3 UTR of MMP3 to suppress the expression of MMP3.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, miR-17-5p was also decreased in hBMECs in response to meningitic E. coli infection, as observed in our previous work [46]. Here, we showed that miR-17-5p was one of the competitive-sponging targets of lncRSPH9-4 and miR-17-5p could bind to 3 UTR of MMP3 to suppress the expression of MMP3.…”
Section: Discussionsupporting
confidence: 91%
“…As accumulating evidences suggest, circRNAs can act as miRNA sponge to regulate various biological processes and gene expression [ 33 , 34 ]. In the present research, it was verified that hsa_circ_0007292 owned the stable circular structure and predominantly located in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…suis induction of BBB disruption is a complex process between the host and pathogen. Many studies have reported that as the most important junctional structure of BBB, the TJ proteins play important roles in maintain BBB integrity and stability of CNS microenvironment [17,54,55].…”
Section: Discussionmentioning
confidence: 99%